The Influence Of Content Marketing And Customer Relationship Management Towards Brand Image And Brand Loyalty (An Empirical Study Of The Brand Zalora Indonesia In Pontianak) - Runi, Runi Virzia Mutiari B1024131008 (Jurnal Manajemen Update, 2017)
The presence of social media platforms has taken over the world and affecting customer’s purchase behavior. Customers face a lot of options in terms of choosing a product from various brands, and it makes the market becomes more competitive than ever. It drives the existence of social media advertising, a way to do marketing strategies using social media platforms to reach more and more potential customers.  Content marketing appears to be one of many social media marketing strategies to engage customers and do advertisement differently. On the other hand, with a lot of options customers are able to pick, it is quite a challenge for a brand to keep their customers to be loyal with the brand. Hence, Customer Relationship Management (CRM) becomes one of the powerful tools to maintain a beneficial and long lasting relationship with customers. This study aims to analyze the influence of both content marketing and the practice of CRM towards customers’ loyalty towards a brand, with an interference of brand image. The sample of this study consists of 100 respondents who are active social media users who had purchased products from Zalora Indonesia repeatedly. The data were processed using SPSS 17 and analyzed with path analysis method. It is found that content marketing doesn’t have a significant influence towards brand loyalty, but it does significantly influence the brand image. CRM has a significant influence towards both brand image and brand loyalty, and on the other hand brand image does have a significant influence on brand loyalty.Keywords: content marketing, customer relationship management, brand image, brand loyalty